A prisoner of birth - Archer, Jeffrey, 1940- (St. Martin's Press, 2008)
A man framed for the murder of his best friend seeks revenge against the four men who put him in Belmarsh prison, the highest-security jail in the land, from where no inmate has ever escaped.